The use of psychotropic medications in autistic individuals (21 years and younger) in Western Australia: A preliminary investigation. - Bulonza, Roselyne; Watkins, Kim; Parsons, Richard; Sunderland, Bruce; Whitehouse, Andrew; Caccetta, Rima (2024)
Prescriptions and use of medications to treat mental health conditions in young autistic populations are inconsistent worldwide. This makes it hard to compare findings from international studies to the Australian autistic population, where there are limited relevant studies. Apart from risperidone, there are no other medications specified for direct use in autistic persons. This study aims to gain initial broad understanding of the use of medications, commonly prescribed for mental health conditions, specifically by autistics under the age of 21 years. We analysed data that were previously collected as part of the Western Australian Autism Biological Registry between 2011 and 2015 which amounted to 239 surveys completed on young persons with diagnosed autism. The questionnaires included information on co-occurring conditions, current or previous use of medications and reasons for use of the medications. Only one-quarter of the participants in this study reported using at least one mental health-related medication in their lifetime. The most reported medications were stimulants, antidepressants and antiepileptics. The reasons for using medication included managing attention deficit hyperactivity disorder, challenging behaviours, seizures, sleep difficulties and symptoms of anxiety and depression. The number of individuals reporting medication use in this study was lower compared to other developed countries. Nevertheless, these medications should be monitored due to limited understanding of their use to manage co-occurring symptoms in young autistic persons. The findings highlight the importance of ongoing research to better understand mental health-related medications and inform best practice.